Relationships between the large‐scale atmosphere and the small‐scale convective state for Darwin, Australia. Issue 20 (25th October 2013) - Davies, L.; Jakob, C.; May, P.; Kumar, V. V.; Xie, S.
<x xml:space="preserve">Abstract</x> [1] A persistent problem for numerical weather and climate models is the representation of tropical convective precipitation which for the most part occurs on spatial and temporal scales too small and too short to be explicitly resolved. Given that model parameterizations represent this subgrid convection as a function of the large‐scale atmospheric state, an understanding of the strongest relationships between the two scales is needed. This study introduces a method to create two concurrent long‐term data sets that describe both the large‐scale atmosphere and the characteristics of the small‐scale convection. Important relationships between these two scales are then investigated. It is found that convective precipitation, through convective precipitation area, has the strongest relationship with dynamical variables such as moisture convergence and vertical velocity at midlevels. The magnitude of the fluctuations of convective strength about the mean is found to be anticorrelated with the strength of the large‐scale variables, indicating a more stochastic behavior of tropical convection in weakly than strongly forced regimes, respectively. Atmospheric stability related variables are not found to be positively related to either convective precipitation area or convective precipitation intensity, which is often an assumption made in convective parameterization. On the contrary, in a more unstable atmosphere, there is lower convective precipitation.